UMP hub for MyREN IPT East Coast access - Mohd Rashid, Abu Bakar (2021)
PEKAN, 11 October 2021 - The relocation of the East Coast Malaysian Research & Education Network (MyREN) Point-of-Presence (PoP) from Universiti Malaysia Pahang (UMP) Gambang campus to UMP Pekan will improve PoP operations.